Innovations and Hurdles in Digital English Learning: A Hospitality Education Perspective - Purwanto, M Bambang; Umar, Umar (Jolly Journal of English Education, 2024)
The hospitality industry in the digital era requires its staffto have qualified English skills. This study examines thechallenges and opportunities for students of the D3Hospitality Study Program at Prasetiya MandiriPolytechnic in learning English in the digital era. Theresearch method used is a prospective case study with aqualitative approach. Data was collected through in-depthinterviews with students, lecturers, and hotel staff. Thestudy results show that D3 Hospitality students facevarious challenges in learning English in the digital era,such as the ease of being distracted by gadgets, difficultychoosing quality learning materials, and lack of motivationto study independently. On the other hand, the digital eraalso offers various opportunities to improve Englishlearning, such as easy access to learning materials,different learning methods, and global interaction withnative English speakers. Based on the findings of theresearch, practical strategies were formulated to improveEnglish learning at D3 Hospitality of Prasetiya MandiriPolytechnic in the digital era, namely: (1) the use ofexciting and interactive educational technology, (2) thedevelopment of learning materials that are contextual andrelevant to the needs of the hospitality industry, (3)increasing students' motivation to learn independently,and (4) the creation of a positive English learning culturein the study program environment